MACA / Juaini Jamaludin... [et al.] - Jamaludin, Juaini; Adnan, Nurul Atikah; Ibrahim, Siti Fairuz; Shawalludin, Syahrini; Badri, Zawani (Universiti Teknologi MARA, Kedah, 2018)
•MACA' is a new app created with the aim of helping students to have an online learning platform for •VCS 265' Contemporary Art & Design in Malaysia course. It enables students to do their revision at anytime, anywhere. The Malaysia Education Blueprint 2015-2025 (Higher Education) has highlighted ten shifts to be achieved in education system and one of aspirations is for students to induce continuous excellence in education. This app is designed in line with one of the shifts under MEB (HE) which is to globalise online learning and make it as an essential component in higher education. Besides, this apps has the potential of meeting one of the demands on Industry (IR) 4.0 which is big data analytics. There are two main features included in the app which are notes in slide show presentaion and exercises. Interactive notes related to VCS265 Contemporary Art & Design in Malaysia is the first key feature of this app, followed by several excercises containing fifteen questions that are randomly chosen for each chapter. Besides. the tool that is used for building this app Is Macromedla Flash. This app is user-friendly and feasible, since most of the students own at least a smartphone and this allows them to access this app at their convenience. One of the outcomes is aimed to target the students who have lack interest in Malaysia's history of contemporary art and design, with the hope that this will encourage the students to be more confident to learn and excel an history and appreciation excercises with ease.